Improving Glycemic Control Among Indonesian Urban Adults: A Digital and Behavioral Extension of the Information–Motivation–Behavioral Skills Model - Appulembang, Imelda (Kesmas, 2025)
Management of type 2 diabetes mellitus (T2DM) in Indonesia continues to face challenges due to behavioral, informational, and technological gaps among patients. This study analyzed the influence of self-regulatory competence and information, motivation, family support, and digital health literacy on glycemic control behavior. A cross-sectional survey was conducted from February to April 2025 among 587 adults aged >30 years with T2DM enrolled in the Chronic Disease Management Program at primary health care in six major cities: Jakarta, Surabaya, Yogyakarta, Medan, Makassar, and Banjarmasin. Data were collected through structured questionnaires and analyzed using partial least squares structural equation modeling. The findings revealed that motivation, followed by information and family support, exerted the strongest effect on self-regulatory competence. Self-regulatory competence significantly predicted glycemic control behavior, whereas digital health literacy directly improved behavior and strengthened the effect of self-regulatory competence. These results suggested that behavioral competence and digital engagement were mutually reinforcing capacities essential for the self-management of chronic diseases. This study extends the Information–Motivation–Behavioral Skills model by incorporating digital and social dimensions, offering a contextually grounded framework for strengthening diabetes care in Indonesia’s urban health system.